Does globalization impede environmental quality in India? - Nanthakumar, Loganathan; Muhammad, Shahbaz; Hrushikesh, Mallick (2015)
Using annual data for the period 1970-2012, the study explores the relationship between globalization and CO2 emissions by incorporating energy consumption, financial development and economic growth in CO2 emission function for India. It applies Lee and Strazicich (2013) unit root test for examining the stationary properties of variables in presence of structural breaks and employs the cointegration method proposed by Bayer-Hanck (2013) to test the long-run relationships in the model. The robustness s of cointegration result from the latter model was further verified with the application of the ARDL bounds testing approach to cointegration proposed by Pesaran, Shin and Smith (2001). After confirming the existence of cointegration, the overall long run estimates of the estimation of carbon emission model points out that acceleration in the process of globalization (measured in its three dimensions - economic, social and political globalizations) and energy consumption result in increasing CO2 emissions, along with the contribution of economic development and financial development towards the deterioration of the environmental quality by raising CO2 emissions over the long-run. This finding validates holding of environmental Kuznets Curve (EKC) hypothesis for the Indian context.